Reaching for Yield in Corporate Bond Mutual Funds - Choi, Jaewon; Kronlund, Mathias (Review of Financial Studies, 2018)
We examine “reaching for yield” in U.S. corporate bond mutual funds. We define reaching for yield as tilting portfolios toward bonds with yields higher than the benchmarks. We find that funds generate higher returns and attract more inflows when they reach for yield, especially in periods of low-interest rates. Returns for high reaching-for-yield funds nevertheless tend to be negative on a risk-adjusted basis. Funds engage in rank-chasing behavior by reaching for yield, although these incentives are moderated by the illiquid nature of corporate bonds. High reaching-for-yield funds hold less cash and less liquid bonds, exacerbating redemption risks.